A Randomized Controlled Pilot Trial of the Unified Protocol for Transdiagnostic Treatment of Emotional Disorders in Children. Issue 3 (May 2019) - Kennedy, Sarah M.; Bilek, Emily L.; Ehrenreich-May, Jill
The Unified Protocol for Transdiagnostic Treatment of Emotional Disorders in Children (UP-C) is an intervention for children aged 7 to 13 targeting high negative emotion, emotional reactivity, and emotion regulation deficits common across emotional disorders. Our objective was to collect pilot randomized controlled trial (RCT) data on the efficacy of the UP-C, comparing UP-C with an active, anxiety-focused intervention. Participants were 47 children with at least one primary anxiety disorder; approximately one half had elevated depression symptoms. Participants received either UP-C or the anxiety-focused control treatment. No condition-related differences were found with respect to diagnostic remission and anxiety symptoms. However, differences in favor of UP-C were observed with respect to treatment response at follow-up, depression symptoms, sadness dysregulation, and cognitive reappraisal. Results provide preliminary evidence that the UP-C may be at least as efficacious in treating anxiety as well-supported anxiety-specific treatment protocols and may produce greater gains in certain emotion reactivity and regulation variables.